1992
DOI: 10.1677/joe.0.1340459
|View full text |Cite
|
Sign up to set email alerts
|

The International Standard for Recombinant DNA-derived Erythropoietin: collaborative study of four recombinant DNA-derived erythropoietins and two highly purified human urinary erythropoietins

Abstract: The International Standard (IS) for Recombinant DNA-Derived (rDNA) Erythropoietin (EPO) (in ampoules coded 87/684) and three other rDNA EPO preparations in ampoules coded 87/690, 87/696 and 88/574 respectively, were compared with two preparations of highly purified human urinary (HU) EPO and the 2nd International Reference Preparation of Human Urinary Erythropoietin for Bioassay (2nd IRP) by 26 laboratories in 11 countries using a wide range of in-vivo and in-vitro bioassays and immunoassays. These EPO prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 35 publications
2
41
0
3
Order By: Relevance
“…Combinations of two or three independent bioassays gave potencies and confidence limits for the preparations that satisfied the specifications of the European Pharmacopoeia (15) and gave a precision that agreed with previously published values (13,19). However, by comparing the results and precision of the single injection assay with those of the multiple daily injection assay it can be seen that for the single injection at least two assays were generally necessary to achieve acceptable limits, whereas for the multiple injection assay the confidence intervals were lower, and the precision and reproducibility were higher using results from only one assay.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Combinations of two or three independent bioassays gave potencies and confidence limits for the preparations that satisfied the specifications of the European Pharmacopoeia (15) and gave a precision that agreed with previously published values (13,19). However, by comparing the results and precision of the single injection assay with those of the multiple daily injection assay it can be seen that for the single injection at least two assays were generally necessary to achieve acceptable limits, whereas for the multiple injection assay the confidence intervals were lower, and the precision and reproducibility were higher using results from only one assay.…”
Section: Discussionsupporting
confidence: 83%
“…Currently, the normocythemic mouse bioassay is performed in normal animals with single (13)(14)(15) or multiple injections (16)(17)(18) and the biological activity of rhEPO is measured by the stimulation of reticulocyte production (3,(16)(17)(18). Bioassays, in particular that involving a single injection into normocythemic mice, have been widely applied in standardization studies and in the potency evaluation of pharmaceutical preparations (13,15,19); however, although they are usually robust, some improvement is needed with regard to response variability and accuracy, most importantly when assessing the potency of commercial rhEPO batches from various sources (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo post-hypoxic polycythaemic mouse bioassay (Cotes & Bangham, 1961) was carried out with modifications, as described previously (Storring et al, 1998). All bioassay estimates were in terms of the International Standard for Recombinant DNA-derived Erythropoietin (IS) (Storring & Gaines Das, 1992).…”
Section: Bioassaysmentioning
confidence: 99%
“…In the case of rEPO, the isoform composition is influenced by the cell line and culture conditions used for its synthesis, and the selectivity of the purification procedures used to isolate the preparation. Thus differences have been found between the isoforms of EPOs synthesized in different cell lines, between different products synthesized in the same type of cell line and even between batches of the same product (Sasaki et al, 1987;Wide & Bengtsson, 1990; Rice et al,EPOs differing in their isoform composition have been found to differ in their biological activities (Fukuda et al, 1989;Takeuchi et al, 1989;Storring & Gaines Das, 1992;Storring et al, 1998). However, structure-activity studies among the isoforms of EPO have usually used only chargebased separations by isoelectric focusing (IEF) or electrophoresis to distinguish between the isoform compositions of different EPOs, ascribing observed differences between isoforms mainly to differences in sialylation.…”
mentioning
confidence: 99%
“…It contains both N-linked and O-linked carbohydrates that have been structurally determined (Sasaki et al, 1988). Chinese hamster ovary cell-derived recombinant HuEPO contains similar carbohydrate moieties to that of human urinary EPO, although the carbohydrate on CHO-EPO and other recombinantly produced EPO is different f r o m that of urinary EPO (Storring & Das, 1992). In contrast, the gene product ex-pressed in Escherichia coli (E. coli EPO) is nonglycosylated and has low biological activity in vivo.…”
mentioning
confidence: 99%